2017
DOI: 10.1371/journal.pmed.1002341
|View full text |Cite
|
Sign up to set email alerts
|

Community and health system intervention to reduce disrespect and abuse during childbirth in Tanga Region, Tanzania: A comparative before-and-after study

Abstract: BackgroundAbusive treatment of women during childbirth has been documented in low-resource countries and is a deterrent to facility utilization for delivery. Evidence for interventions to address women’s poor experience is scant. We assessed a participatory community and health system intervention to reduce the prevalence of disrespect and abuse during childbirth in Tanzania.Methods and findingsWe used a comparative before-and-after evaluation design to test the combined intervention to reduce disrespect and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
112
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(143 citation statements)
references
References 34 publications
3
112
1
Order By: Relevance
“…[7][8][9][10][11] These interventions include training health care providers in values and attitudes transformation and communication skills; setting up quality improvement teams; monitoring disrespect and abuse; improving staff conditions; maternity open days; dispute resolution, etc. [7][8][9][10][11] These interventions include training health care providers in values and attitudes transformation and communication skills; setting up quality improvement teams; monitoring disrespect and abuse; improving staff conditions; maternity open days; dispute resolution, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] These interventions include training health care providers in values and attitudes transformation and communication skills; setting up quality improvement teams; monitoring disrespect and abuse; improving staff conditions; maternity open days; dispute resolution, etc. [7][8][9][10][11] These interventions include training health care providers in values and attitudes transformation and communication skills; setting up quality improvement teams; monitoring disrespect and abuse; improving staff conditions; maternity open days; dispute resolution, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Africa suggest that multicomponent interventions can improve various aspects of RMC including reducing disrespect and abuse. [7][8][9][10][11] These interventions include training health care providers in values and attitudes transformation and communication skills; setting up quality improvement teams; monitoring disrespect and abuse; improving staff conditions; maternity open days; dispute resolution, etc. 12 A recent systematic review concluded that while these multicomponent interventions appear to reduce some aspects of disrespect and abuse, their sustainability is unclear and the intervention components with the greatest impact have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the abundance of research on D&A prevalence, few studies have investigated effective measures for reducing and preventing the prevalence of D&A behaviors during labor and birth [17][18][19]. The identification of both aggravating and mitigating factors of negative and abusive care provider-patient relationships has been neglected in health systems.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence shows that the implementation of specialized respectful maternity care programs and interventions that positively in uence the attitude and response of maternity care providers are generally effective in reducing the rate of mistreatment of childbearing women during intrapartum care services in developing countries [9][10][11][12][13][14][15]. Some of these programs and interventions include theatrebased training interventions to reduce obstetric violence [14], monitoring of midwives during practice [9], improvement in working conditions of healthcare providers [11], equipping midwives with the ability to identify and manage obstetric and neonatal emergencies [16], and the training of midwives to effectively communicate with clients [10,17].…”
Section: Introductionmentioning
confidence: 99%